Coupled wind-rain-subsidence effects on soil erosion dynamics in an arid mining area: Insights from CFD-DEM and physical simulations - Chuning Ji; Ziheng Song; Chuanjiu Zhang; Yanli Huang; Ling Wu; Xiaobin Li; Xiaolong Wang; Ruimin He; Yangnan Guo; Jian Zhang; Chuanxu Wang; Yu Tian; et al. (CATENA, 2026)

Biomass carbon dots and oxidized anthocyanins dual-driven strategy: enhanced collagen films for shrimp preservation and colorimetric/fluorescent freshness monitoring - Linjing He; Ruimin Ran; Feizhi Li; Wenli Shi; Yeqing He; Hengjun Xiang; Guoying Li (Food Research International, 2026)

Flocculation performance of a red soil-based inorganic coagulant enhanced by Fe3O4 magnetic loading - Yixuan Huang; Qi Li; Ruimin Zhao; Ruyan Luo; Shaman Zhou; Yuanliang Zhang; Jingbao He; Wanqing Yang; Zhifei Yu; Jiahao Yang; Liang He; Xuyuan Zhao; et al. (Process Safety and Environmental Protection, 2026)

Biomass-derived catalyst for CO2 cycloaddition: High efficiency and low environmental impact - Jiasen He; Ruimin Zhao; Xuran Li; Qiannan Wang; Yumeng Xiao; Yue Wu; Tony D. James; Lidong Wang; Meng Li (Chemical Engineering Journal, 2026)

Biological activities, metabolic profiles, and in vitro uric acid-lowering mechanisms of cell-free supernatant from coconut water by Limosilactobacillus DO28L8 - Xi Zheng; Yanpei Huang; Weijun Chen; Wenxue Chen; Qiuping Zhong; Jianfei Pei; Ying Lv; Rongrong He; Haiming Chen; Ming Zhang; Ruimin Wang (Food Bioscience, 2026)

Collagen films enhanced with bovine hide-tannic acid carbon dots: A traditional tanning-inspired strategy for crispy fried chicken preservation - Linjing He; Ruimin Ran; Xin Guo; Wenli Shi; Zhijie Zhang; Guoying Li (Food Hydrocolloids, 2026)

Responses of Soil Water Infiltration and Recharge to Irrigation Methods in the Semi‐Arid Farming–Pastoral Ecotone of Northern China - Zhenguo Xing; Ruimin He; Jie Fang; Mingzhe Lei; Lu Bai; Xuejia Li; Xiaoqing Liu; Gang Liu; Ming Zhao (Irrigation and Drainage, 2026)
Water scarcity poses a critical challenge in arid regions of northwest China, where suboptimal irrigation practices have led to significant water resource depletion. This study examines soil water transport mechanisms in maize fields under different irrigation regimes in a representative farming‐pastoral ecotone through field monitoring and HYDRUS‐1D modelling during the 2023 growing season (June–September). The results revealed that, compared with conventional flood irrigation, drip irrigation substantially reduced water loss. The total infiltration amount under drip irrigation was 358 mm, of which 196 mm contributed to deep percolation. The total infiltration amount and deep percolation amount under flood irrigation were 588 and 288 mm, respectively. In contrast, drip irrigation significantly reduced these losses, cutting deep percolation by 39% and improving irrigation water use efficiency by 12%. Furthermore, we identified the optimal groundwater depth for maximizing recharge efficiency. Specifically, the optimal groundwater depths were identified as 1.5 m for drip irrigation and 2.0 m for flood irrigation, yielding irrigation infiltration coefficients of 0.46 and 0.65, respectively. These findings provide a scientific basis for developing efficient irrigation strategies and sustainable groundwater management practices in the water‐limited farming–pastoral ecotones of northern China.

Deprotonation-triggered rapid gel coating: Liposome encapsulated luteolin /chitosan enabling dual sustainable food preservation and damage resistance - Wenli Shi; Ruimin Ran; Xin Guo; Linjing He; Guoying Li (Chemical Engineering Journal, 2026)

Development of a dual-layer collagen film with insulating, antioxidant, antimicrobial, and pH-sensitive properties for the maintenance and visual monitoring of shrimp freshness - Ruimin Ran; Xiaoyun Luo; Dongmei Zhai; Yeqing He; Xin Guo; Linjing He; Guoying Li (Food Hydrocolloids, 2025)

Historical evolution and future trend of meteorological drought in the upper Yangtze River basin - Chang Yu; Wenxin Li; Cuishan Liu; Yun Wang; Ruimin He; Guoqing Wang (Climate Dynamics, 2025)

Resolving the Snowball Earth conundrum: the role of marine dissolved organic carbon pool - Bing Shen; Xianguo Lang; Ruimin Wang; Yonggang Liu; Shihong Zhang; Tianzheng Huang; Xuelei Chu; Yixin Cui; Weiming Ding; Yuansheng Du; Ran He; Kangjun Huang; et al. (Science Bulletin, 2025)

Integrating genomic features for prognosis in Chinese patients with B-cell lymphoma following chimeric antigen receptor T-cell therapy - Linghui Zhou; Youqin Feng; Ruimin Hong; Guoqing Wei; Mingming Zhang; Alex H. Chang; He Huang; Yongxian Hu (Science China Life Sciences, 2025)

Coupling coordination degree, interaction relationship and driving mechanism of water resources carrying capacity of Beijing-Tianjin-Hebei urban agglomeration in China - Wentao Xu; Junliang Jin; Jianyun Zhang; Shanshui Yuan; Yanli Liu; Tiesheng Guan; Ruimin He; Liujun Zhu (Journal of Cleaner Production, 2025)

Development of multi-functional collagen films for maintaining and visually monitoring shrimp freshness - Ruimin Ran; YeQing He; Xiaoxia Zhang; Xingling Zeng; Xin Guo; Xiaoyun Luo; Guoying Li (Food Hydrocolloids, 2025)

CdS/NiCoAl-LDH heterojunction for superior photocatalytic hydrogen production and stability in water splitting - Ruimin Yang; Wenning Mu; Longyan He; Junjin Meng; Xiaolong Bi; Wenbin Luo; Shaohua Luo; Xuefei Lei (Chemical Engineering Journal, 2025)

Improving quality profiles of summer-autumn tea through the synergistic fermentation with three fungal strains - Sashuang Dong; Sitong Wu; Ruixin He; Fanyu Hao; Piqian Xu; Minyu Cai; Miao Yu; Ruimin Zhong; Xiang Fang (Food Bioscience, 2024)

A rare KMT2A::CBL transcript in an acute monoblastic leukemia patient with an unfavorable outcome - Jinglei Yu; Fengmei Song; Mingming Zhang; Pingnan Xiao; Jingjing Feng; Ruimin Hong; Yongxian Hu; He Huang; Guoqing Wei (Molecular Biology Reports, 2024)
Background Lysine [K] methyltransferase 2A ( KMT2A , previously known as MLL ) gene rearrangements are common in acute leukemias of various lineages and are associated with features such as chemotherapy resistance and rapid relapse. KMT2A::CBL is a rare fusion of unknown pathogenesis generated by a unique interstitial deletion of chromosome 11 that has been reported across a wide age range in both acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL) patients. The leukemogenic effect of the KMT2A::CBL rearrangement and its association with clinical prognosis have not been well clarified. Methods and results We report the case of a 64-year-old female who was diagnosed with acute monoblastic leukemia (M5a) and who acquired the rare KMT2A::CBL fusion. The patient received multiple cycles of therapy but did not achieve remission and eventually succumbed to severe infection and disease progression. Additionally, we characterized the predicted KMT2A-CBL protein structure in this case to reveal the underlying leukemogenic mechanisms and summarized reported cases of hematological malignancies with KMT2A::CBL fusion to investigate the correlation of gene rearrangements with clinical outcomes. Conclusions This report provides novel insights into the leukemogenic potential of the KMT2A::CBL rearrangement and the correlation between gene rearrangements and clinical outcomes.

Elevated temperature affects the expression of signaling molecules in quail testes meiosis I prophase, but spermatogenesis remains normal - Qianwen Chang; Jiarong Li; Zihui Zhao; Qi Zhu; Yaning Zhang; Ruimin Sheng; Ziyin Yang; Mingcheng Dai; Pengchao Wang; Xiaorui Fan; Junping He (Theriogenology, 2024)

Lactic acid bacteria fermentation improves physicochemical properties, bioactivity, and metabolic profiles of Opuntia ficus-indica fruit juice - Huixian Wang; Xingqiao He; Juanni Li; Jintao Wu; Shuaiming Jiang; Hui Xue; Jiachao Zhang; Rajesh Jha; Ruimin Wang (Food Chemistry, 2024)

Evaluation and analysis of spatio-temporal variation of water resources carrying capacity and restraining factor: a case study in Anhui Province, China - Wentao Xu; Junliang Jin; Jianyun Zhang; Yanli Liu; Zhangkang Shu; Guoqing Wang; Zhenxin Bao; Cuishan Liu; Tiesheng Guan; Ruimin He (Mitigation and Adaptation Strategies for Global Change, 2024)

1.5℃ and 2.0℃ of global warming intensifies the hydrological extremes in China - Zhangkang Shu; Junliang Jin; Jianyun Zhang; Guoqing Wang; Yanqing Lian; Yanli Liu; Zhenxin Bao; Tiesheng Guan; Ruimin He; Cuishan Liu; Peiran Jing (Journal of Hydrology, 2024)

Imbalance of T follicular helper cell subsets trigger the differentiation of pathogenic B cells in idiopathic membranous nephropathy - Bishun Deng; Huijie Huang; Li Deng; Ziling Zhao; Miao Liu; Haibiao Lin; Xiaowan Wang; Ruimin Tian; Xiaoxin Tu; Anping Peng; Enyu Liang; Kun Bao; et al. (Inflammation Research, 2024)

Occurrence and characteristics of microplastics in soils from greenhouse and open-field cultivation using plastic mulch film - Ruimin Qi; Yuanyuan Tang; Davey L. Jones; Wenqing He; Changrong Yan (Science of The Total Environment, 2023)

Assessment of future eco-hydrological regime and uncertainty under climate changes over an alpine region - Lin Wang; Jianyun Zhang; Zhangkang Shu; Zhenxin Bao; Junliang Jin; Cuishan Liu; Ruimin He; Yanli Liu; Guoqing Wang (Journal of Hydrology, 2023)

Assessment of carbon sink potential and methane reduction scenarios of marine macroalgae (Gracilaria) cultivation - Yifan Xu; Huanping Liu; Yufeng Yang; Hongtao Shen; Ruimin Zhang; Cheng Wang; Zhijian Huang; Jianguo He; Zhili He; Qingyun Yan (Science China Earth Sciences, 2023)

A Benzothidiazole-Based Reversible Fluorescent Probe with Excellent Performances in Selectively and Sensitively Sensing of Hg2+ in Water - Bo Yu; Ruimin Yuan; Tianzhi He; Lijuan Liang; Kun Huang (Journal of Fluorescence, 2022)

Understanding the hierarchical controls of geographical features on hydrological responses in humid mountainous areas through a stepwise clustering scheme - Yaqian Yang; Jintao Liu; Shuang Yang; Ruimin He (Stochastic Environmental Research and Risk Assessment, 2022)

Cross-resistance and lack of fitness costs occurred in the cyantraniliprole-resistant oriental fruit fly - Zhang Ruimin; He Shiyu; Zeng Jiwu; Chen Jiahua; Dong Junfeng (Phytoparasitica, 2021)

Impact of temporal rainfall resolution on daily streamflow simulations in a large-sized river basin - Xiaogang Li; Suzhen Huang; Ruimin He; Guoqing Wang; Mou Leong Tan; Xiaoying Yang; Zheng Zheng (Hydrological Sciences Journal, 2020)

Stochastic sensitivity analysis of nitrogen pollution to climate change in a river basin with complex pollution sources - Xiaoying Yang; Lit Tan; Ruimin He; Guangtao Fu; Jinyin Ye; Qun Liu; Guoqing Wang (Environmental Science and Pollution Research, 2017)

Runoff sensitivity to climate change for hydro-climatically different catchments in China - Guoqing Wang; Jianyun Zhang; Ruimin He; Cuishan Liu; Tao Ma; Zhenxin Bao; Yanli Liu (Stochastic Environmental Research and Risk Assessment, 2017)

Establishment of a picloram-induced somatic embryogenesis system in Vitis vinifera cv. chardonnay and genetic transformation of a stilbene synthase gene from wild-growing Vitis species - Lingmin Dai; Qi Zhou; Ruimin Li; Yangjian Du; Jing He; Dan Wang; Siyan Cheng; Jianxia Zhang; Yuejin Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)